First-time mothers’ expectations of the unknown territory of childbirth: uncertainties, coping strategies and ‘going with the flow’ - Borrelli, Sara E.; Walsh, Denis; Spiby, Helen (Elsevier, 2018)
Objective. To explore first-time mothers’ expectations of labour and birth, coping strategies they adopt during pregnancy towards childbirth and coping strategies they expect to use during labour and birth.